Microscopic detection of L.D. bodies in splenic aspirates at Rajshahi Medical College Hospital - Salam, Md. Abdus; Ahmed, Iftikhar; Ali, M S; Hossain, S M A; Begum, Shahanara (Teachers Association of Rajshahi Medical College, 2003)
Leishman stained smears prepared from ninety-nine (99) splenic aspirates and eleven (11) slit skin were examined under light microscope in order to detect L.D. bodies at the department of Microbiology, Rajshahi Medical College from 2002 to May 2003. L.D. bodies were found in 46 (46.46%) and 01 (9.09%) samples of splenic aspirates and slit skin smears respectively. Smear positivity and concomitant higher parasitic load was noted among comparatively younger age groups with slight male preponderance. Demonstration of parasitic by direct microscopical examination in splenic aspirates for the diagnosis of visceral leishmaniasis or kala azar and in slit skin smears for Post kala azar dermal leishmaniasis (PKDL) is reliable method.